Australian history now - Clark, Anna, 1978-; Ashton, Paul, 1959- (NewSouth Publishing, 2013)
Australian history has changed drastically over the last fifty years and has found itself at the centre of heated and consuming public debates. So how do historians themselves read this history? Where do they see themselves in these momentous shifts in historical reading and writing? With contributions from prominent historians including Marilyn Lake, Tom Griffiths, Peter Stanley and Ann Curthoys, Australian History Now offers revealing and refreshing accounts of the ways Australian historians think about the nation¿s past. Australian History Now is an engaging and often surprising introduction to the ways we understand and write our history in academic, popular and school books, argue about it in the media, present it in museums and watch it on television. At its heart it shows that the way we remember our past reflects how we see ourselves in the present.